Práticas educativas de normalistas no Cariri cearense (1923 – 1971): cadernos escolares - escritas femininas - Noronha, Isabelle de Luna Alencar (2015)
This research aims to endorse, regarding to cultural history, the argument that the dissemination of ideas by normalistas masters in Cariri from Ceará state was originated, among other experiences, from their education process that happened during a bigger patriotic-feeling development project, which had also moral and civic aspects for Brazil, under the guardianship and unlimited support of Catholic Church. Thus, it was considered the fact that in Cariri from Ceará state, the first settlement of Normal Course happened under the auspices of Catholic Church. The person behind it was the first bishop from Crato’s diocese (1914), Dom Quintino de Oliveira e Silva, who founded the St. Terese of Jesus Daughters Congregation - S.T.J.D.C (Congregação das Filhas de Santa Teresa de Jesus – C.F.S.T.J.). These people became in charge of St. Terese of Jesus School – S.T.J.S (Colégio Santa Teresa de Jesus – C.S.T.J.), also founded by the bishop in the same day as the Congregation, with the goal to give Cariri from Ceará, focusing on Crato city, an educational institution dedicated to women education. This research is divided in two parts. The first one analyses institutional notebooks from that school, discusses both the history of S.T.J.S. and the settlement of Normal Course in Cariri from Ceará, regarding to the educational procedures that Normalistas masters disseminated. The second section of this research analyses the representation of educational procedures through school notebooks that escaped from their natural destination: disappearance. From those notebooks, it was noticed some contents and teaching organization schemes, procedures and educational practices in which the patriotic, civic and religious ideas were present in developing a new teaching based in “new catholic pedagogy”.